NUMERICAL AND EXPERIMENTAL METHODS USED ON PLASTIC MATERIALS TO IMPROVE KNOWLEDGE ABOUT BIOMECHANICS OF THE MASTICATORY SYSTEM - Mocanu-Brânză Raluca Cristina; Condurache Gabriel Giani; Earar Kamel; Mârțu Silvia; Mocanu Costel Iulian (Romanian Society of Oral Rehabilitation, 2023)
Knowing the functioning of the masticatory system implies, in the last decades, knowledge of dental medicine as well as the mechanics of deformable solids. Thus, a new Biomechanics science appeared, which represents a natural science that studies the objective laws of the movement of living material bodies and the structures that contribute to these movements [1, 2, 3, 4]. Referring to the masticatory system, we have in mind the science of Biomechanics of the masticatory system. This new science combines knowledge from the dental medical field with that from the field of mechanical engineering, the mechanical knowledge complementing and often anticipating the knowledge of dental medicine. In this paper, the efforts of the PhD students are presented in order to elucidate the mechanical behavior of different values of the loads of a mandible. Thus, using numerical methods, the efforts that appear in various phases of the masticatory process can be determined. As these numerical methods are approximate countless times they are complemented by experimental modeling intended to confirm or refute the numerical modeling. Although experimental modeling involves important costs, often these are absolutely necessary to fully elucidate the results of numerical modeling.